PENGARUH NILAI OBLIGASI SYARIAH, RATING OBLIGASI SYARIAH, UMUR OBLIGASI SYARIAH TERHDAP REAKSI PASAR MODAL - vina Indah Iswara; Jeni Susyanti; M. Agus Salim (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThe purpose of this research is to analyze how influence on partial effect of Islamic Bonds (sukuk) value on the capital market reaction, rating of Islamic Bonds (sukuk) on the capital market reaction, age of Islamic Bonds (sukuk) on the capital market reaction. The population that used in this study was Islamic Bonds and listed in the Indonesia Stock Exchange (BEI) in 2013-2017 with 62 Islamic Bonds. The sample selected by purposive sampling. Based on the criteria in the sample selected were 35 Islamic Bonds. The analysis methods used were multiple linear regression method and classic assumption test with hypothesis test used by t test. The analysis equipment used was SPSS 21.The results of the study indicated that Islamic Bonds value have positive and significant effect on the capital market reaction. Rating of Islamic Bonds have negative and significant effect on the capital market reaction. Age of Islamic Bonds did not have significant effect on the capital market reaction.Keywords : Effect of Islamic Bonds, Rating of Islamic Bonds, Age of Islamic Bonds, Capital Market Reaction.